Who is in the driver's seat? Markups, markdowns, and profit sharing in the car industry - Nadine Hahn (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
I develop a general framework for markup and markdown estimation that allows for profit sharing along value chains without making assumptions on conduct between vertically related firms. I derive the conditions under which the markup and markdown estimates relate to the firms' equilibrium bargaining weights. To account for vertical and horizontal product differentiation in the production function estimation, I include plant-level prices and employ car characteristics as demand-based quality controls. Between 2002 and 2018, the European car manufacturers' margins on their input and product markets combined were stable around 10% to 15% on average. The manufacturers' share of the margin on the input market, however, depends on the car segments in which they produce. The suppliers' share depends negatively on the variety of their product portfolio and depends positively on their relationship intensity to car manufacturers. The analysis shows that the manufacturers' bargaining weights decreased during crisis years, such as the financial crisis in 2007 or the dieselgate scandal in 2015.
Keywords: D22; L13; L14; L62; 330; Market Power; Markups; Markdowns; Production Approach; Car Industry; Vertical Chains